Underemployment Rate by Gender in 2015-2018 - Nicholas Renaldo; James; Alan; Nabila Wahid; Cecilia (Interconnection: An Economic Perspective Horizon, 2023)
Understanding the dynamics of underemployment across gender is critical not only for economic policymakers but also for advocates of gender equality. The findings from this analysis can reveal potential areas where targeted interventions and policy measures may be needed to ensure that both men and women have equal opportunities for full and meaningful employment. This study uses a quantitative approach. This study uses data on underemployment rate by gender provided by the Central Bureau of Statistics. The study employs a Contingency Table Analysis, specifically utilizing the chi-square test. Contingency Table Analysis suggests that there is no substantial relationship between the level of underemployment by gender during the specified years, it is important to approach this conclusion with caution due to the limitations of the analysis and the possibility of unaccounted influences. Further research, possibly incorporating additional variables and a more extended time frame, would be valuable for a comprehensive understanding of the complex relationship between underemployment, gender, and regional factors.